Integrated Geophysical Data and GIS Technique to Forecast the Potential Groundwater Locations in Part of South Eastern Nigeria - Agbasi, Okechukwu Ebuka; Aziz, Nadia Ahmed; Abdulrazzaq, Zaidoon Taha; Etuk, Sunday Edet (Iraqi Journal of Science, 2019)
The objective of this research is to select the most suitable drilling location of new groundwater exploration wells, with a decision-making tool from Geographic Information System (GIS). The optimum location will be evaluated base on the hydro-geoelectrical parameter derived from Vertical Electrical Sound (VES) including Longitudinal Conductance, the thickness of the aquifer, the apparent resistivity and Transmissivity. From the Geo-electrical method (VES) the finds shows that the aquifers in the study area have Apparent Resistivity ranging from 0.32 to 40.24 Ωm, Thickness between 0.21 m to 15.06 m, Longitudinal Conductance ranging from 0.006 to 10.246Ω-1 and Transmissivity ranging from 0.14 to 10.38m2/day. Hydro-geoelectrical data were integrated into GIS to precisely determine the best location for groundwater borehole. Finally, the study location was classified into three classes; not suitable, moderately suitable and highly suitability with respect to the input factors using the Fuzzy overly combing method. It’s evident that the middle part of the area in study represents the optimum location for the drilling of groundwater boreholes.